If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4r = -3 + 7r Solving 4r = -3 + 7r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-7r' to each side of the equation. 4r + -7r = -3 + 7r + -7r Combine like terms: 4r + -7r = -3r -3r = -3 + 7r + -7r Combine like terms: 7r + -7r = 0 -3r = -3 + 0 -3r = -3 Divide each side by '-3'. r = 1 Simplifying r = 1
| -70-5= | | -80-(-40)= | | X=320000 | | X=320000 | | (8x^4)(2x^3)= | | t=10+5 | | 17=c+10 | | x+y=320000 | | 5b+6-6b+r=19 | | 3j-8=5j+4 | | 5.4=3s | | x-69=-6x+99 | | -9=-6+3(5-m) | | 7(7x+5)=7(x-1) | | 5x-111=-7x+105 | | x=180-88 | | x+3.5=10.2 | | 2=3x-10 | | 4=14-k | | -2s-14s-5=11 | | -3t+7=-8t-3 | | 2d+d-3=6 | | p-7=-5 | | -4x+9(x-3)=10x+2 | | 20=8(v-90)-52 | | 3n+6=-10n-7 | | -10q-(-19q)-(-8)=17 | | 10-(-4)= | | 14n-13n=17 | | 3x(x-5)=2(x+4) | | 3=-(x+5) | | 4f=9+5f |